ACOX1 deficiency-induced lipid metabolic disorder facilitates chronic interstitial fibrosis development in renal allografts - Yang-He Zhang; Bin Liu; Qingfei Meng; Dan Zhang; Hongxia Yang; Guangtao Li; Yuxiong Wang; Mingdi Liu; Nian Liu; Jinyu Yu; Si Liu; Honglan Zhou; et al. (Elsevier, 2024)
Chronic interstitial fibrosis presents a significant challenge to the long-term survival of transplanted kidneys. Our research has shown that reduced expression of acyl-coenzyme A oxidase 1 (ACOX1), which is the rate-limiting enzyme in the peroxisomal fatty acid β-oxidation pathway, contributes to the development of fibrosis in renal allografts. ACOX1 deficiency leads to lipid accumulation and excessive oxidation of polyunsaturated fatty acids (PUFAs), which mediate epithelial-mesenchymal transition (EMT) and extracellular matrix (ECM) reorganization respectively, thus causing fibrosis in renal allografts. Furthermore, activation of Toll-like receptor 4 (TLR4)-nuclear factor kappa-B (NF-κB) signaling induced ACOX1 downregulation in a DNA methyltransferase 1 (DNMT1)-dependent manner. Overconsumption of PUFA resulted in endoplasmic reticulum (ER) stress, which played a vital role in facilitating ECM reorganization. Supplementation with PUFAs contributed to delayed fibrosis in a rat model of renal transplantation. The study provides a novel therapeutic approach that can delay chronic interstitial fibrosis in renal allografts by targeting the disorder of lipid metabolism.